2006
DOI: 10.1007/bf03325947
|View full text |Cite
|
Sign up to set email alerts
|

Correlations, partitioning and bioaccumulation of trace metals between different segments of Taylor Creek, southern Nigeria

Abstract: ABSTRACT:Correlations between trace metals in dissolved and particulate phases, B. bayad and sediments were investigated in five selected sites along Taylor Creek, which lies between longitude 006°17I to 006°21 I E and latitude 05°01 I to 05°05 I N. The degree of correlation between the various metals was different in each of the investigated segments. Between segments, not many significant correlations were recognized. Only Ni and Cd, Mn and Cd, Mn and Ni, and Mn and Pb are correlated in the sediments and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…In addition, the higher electrical conductivity observed at S 2 could be attributed to the relatively low DO concentration and revealed high negative correlation to each other (temp/DO: r= -0.771). This result is in accordance with the works of Phiri et al [21] and Okafor [22] who reported that high EC contribute for reduction of DO concentration in the given water bodies.…”
Section: Physicochemical Charactersticssupporting
confidence: 93%
“…In addition, the higher electrical conductivity observed at S 2 could be attributed to the relatively low DO concentration and revealed high negative correlation to each other (temp/DO: r= -0.771). This result is in accordance with the works of Phiri et al [21] and Okafor [22] who reported that high EC contribute for reduction of DO concentration in the given water bodies.…”
Section: Physicochemical Charactersticssupporting
confidence: 93%
“…High concentration of copper observed in the sediment was probably due to high anthropogenic and natural processes. This is in accordance with the observation by (Hughes and Plos, 1978, Bezuidenhout et al, 1990, Seymore, 1994, Oronsaye and Ogbebo, 1995, Senthil et al, 2008, Horsfall and Spiff, 2002, Okafor and Opuene, 2006, who stated that copper mainly accumulated in sediment.…”
Section: Kpee F; Ekpete Oasupporting
confidence: 80%
“…The BCF and BMF were metal-and organism-dependent (Okafor and Opuene 2006). BCF represents the uptake of metals into an organism from the surrounding water alone.…”
Section: Resultsmentioning
confidence: 99%
“…The treatment of B. bayad samples was based on an established procedure (Okafor and Opuene 2006). Before analysis, the catfishes were dehydrated to a constant weight using an oven at 65°C for 20 h and individual whole fish pulverised to a uniform particle size.…”
Section: Sample Treatment and Analysismentioning
confidence: 99%
See 1 more Smart Citation